External Factors Affecting Da'if Hadith Validity: A Study on 'The Talqah of the Ummah in Al-Qabul' and Water Purity Changes - Abdurrohman, Irwan; Mubarok, Muhamad Raihan Syahrul (Jurnal Iman dan Spiritualitas, 2025)
This research aims to analyze the concept of the validity of "talaqqathu al-ummah bi al-qabul", with a focus on the case of the hadith regarding changes in the purity of water due to impurity entering it which changes its smell, color and taste. This research uses a qualitative approach with a literature study method. Data was collected through analysis of hadith books, primary sources of hadith, and fiqh literature. The research results show that there is a concept of external validity used by hadith experts, namely the concept of "talaqqathu al-ummah bi al-qabul." In the case of the hadith on changing the purity of water, even though the sanad is considered da’if, al-Shafi'i and al-Baihaqi judge it to be authentic because of the ijma that strengthens it. This research has implications for a broader understanding of the external hadith validity criteria used by hadith experts.